Simposium Kebudayaan Indonesia- Malaysia Ke -11 Bandung, Indonesia 10-12 November 2009 - Rapeah, Suppian (Pusat Pengajian Sains Kesihatan, 2009)
Malaria is one of the most devastating infectious diseases affecting much of the underdeveloped world with approximately 300-500 million people displaying clinical manifestations each year. Plasmodium falciparum is responsible for more then 90% of malaria cases in Africa and accounts for more than one million deaths annually. Due to the emergence of insecticide-resistant mosquito · vectors and chloroquine-resistant parasites in many parts of the world as well as the complexity of the parasite life cycle, the development of a safe and effective malaria vaccine is urgently need to fight against malaria. DNA vaccines have already been applied to deliver foreign antigens to the immune system in a wide range of infectious diseases including malaria. In this study, a DNA vaccine expressing the synthetic epitope of Plasmodium falciparum F2R(II)EBA • has been constructed. Immunogenicity study in Balb/c mice showed that the candidate vaccine is able to induce hwnoral immWle response against the epitope. This study demonstrated the potential of using DNA vaccine to protect against malaria infections in humans in the near future.